Morpho-physiological and Molecular Characterization of Pearl Millet [Pennisetum glaucum (L.) R. Br.] Germplam Lines for Drought Tolerance - M. L. Choudhary; M. K. Tripathi; Sushma Tiwari; R. K. Pandya; Neha Gupta; Niraj Tripathi; Prerana Parihar (New Visions in Science and Technology Vol. 5, 2021)
Objectives: The present investigation was commenced to analyze presence of possible genetic diversity among different pearl millet germplasm lines by means of diverse drought linked morpho-physiological traits along with SSR molecular markers. Study Design: In the present investigation, 96 pearl millet germplasm lines were screened against drought using different morphological and physiological traits along with SSR markers. Place and Duration of the Study: The present study was conducted at College of Agriculture, Gwalior, Rajmata Vijayaraje Scindia Krishi Vishwa Vidyalaya, Gwalior, M.P., India during July 2019 to December, 2020. Methodology: The study was conducted to record different morphological and physiological traits related to drought tolerance and susceptibility. Thirty-five microsatellite markers were also used in laboratory to analyze the variability among pearl millet genotypes under study. Results: Pearl millet genotypes were grouped according to their morpho-physiological characteristics. Among 35 SSR markers, twenty-two were successfully amplified across all germplasm lines and seven SSR markers were found to be polymorphic and fifteen markers were monomorphic. All seven polymorphic SSR markers were used consequently for amplification of all the 96 germplasm lines. The range of PIC value was 0.0939 to 0.2980 with an average of 0.2274. The highest PIC value was recorded for the markers Xibmsp26 and Xibmsp29 (0.2980) followed by Xibmsp03 (0.2392), Xibmsp29 (0.2392), Xibmsp06 (0.2289) and Xibmsp07 (0.1948) while the lowest for the marker Xibmsp01 (0.0939). The range of major allele frequency value was 0.7604 to 0.9479 with an average of 0.8363. The range of genetic diversity value was 0.0987 to 0.3644 with an average of 0.2665. Conclusions: According to the morpho-physiological data a total of 22 pearl millet genotypes were found to be grouped distantly from rest of the genotypes. These genotypes may be drought tolerance as they are linked with drought tolerant morpho-physiological traits however, rests of the genotypes were found to be susceptible against drought.